Morphological features of rye grain with low pentosan content - V. D. Kobylyansky; O. V. Solodukhina; I. M. Nikonorova (Труды по прикладной ботанике, генетике и селекции)
Background. The grain coat plays a major role in the development of rye cultivars with low levels of water-soluble pentosans (WSP). Grain coat thinness is a diagnostic trait for low WSP (arabinoxylans) content. To improve the technology of low-pentosan rye breeding, it becomes important to study the effect of changes in the anatomy of low-pentosan grains on morphological characteristics.Materials and methods. Grains with thin coats (transparent) were identified with the LFS-1 diaphanoscope in the populations of 7 commercial winter rye cultivars grown in Russian Federation. Anatomical and morphological features of seed coats were studied on thick- and thin-coated grains identified in the rye cultivars ‘Era’ and ‘Vyatka’. The thickness of grain coats and the aleurone layer were assessed according to L. N. Lyubarsky.Results and conclusions. In thin-coated rye grains, we found a reduction in the thickness of the pericarp and seed coats by 50–70% and in the aleurone layer by 32.1–39.6%, compared to thick-coated grains. With a constant cell size in “transparent” grains, a decrease in the thickness of the aleurone layer and coat occurs at the expense of the reduction in not only the cell walls, but also the intercellular space. The pericarp in the tissues of the second multicellular layer contains the bulk of the protective biologically passive WSP. It was proved that there were no significant changes in grain parameters, such as length, width and relative volume, depending on coat thinness. Significant differences were found in the 1000 grain weight. In “transparent” grains the index increased by 5.2–19.7%, compared with “nontransparent” ones.